The problem of violation of the system implementation of the psycho-semantic and psycholinguistic requirements for brand name - I. Yu. Aleksandrova (Вестник университета)
The analysis and systematization of psychosemantic, psycholinguistic, including phonosemantic requirements to the name of the trademark have been carried out, the problem of their unsystematic practical implementation have been considered. The article presents the results of an empirical study conducted by the author aimed at identifying the degree of psychological acceptability of the brand name actually existing on the Russian market. As a result of the analysis of the primary data, the author reconstructs the associative field of the diagnosed word-name, the specific semantic content of which proves the need for a preliminary check of the communicative efficiency of the brand name. The presented method can be used for practical purposes in the process of naming.